Evaluation of Converting an AC Distribution Cabinet to DC Operation - Fathi Haft Chesheme, Daniel (My University, 2026)
These days, the rapid growth of loads based on direct current has increased quickly. Loads such as EV chargers, photovoltaic systems, energy storage systems, and power electronic equipment have made the use of DC distribution systems at the low-voltage level more important. DC system helps to avoid several conversion of AC/DC conversion, which reduces losses, makes the system simpler, and increases the overall e!ciency. In this thesis, the consequences of converting a three-phase AC cabinet to a proposed bipolar DC structure cabinet have been investigated. A comparison between these two systems has been performed in terms of power transfer, power losses, thermal behavior, e!ciency, insulation stress, cable structure, protection, and environmental impacts. The results show that the DC structure can transfer higher active power at the same rated current, and also, because of using fewer conductors and removing e"ects such as reactive power and power factor, the conduction losses in the system are reduced, which leads to lower temperature inside the cabinet and higher overall system e!ciency. Despite these advantages, converting the AC system to DC has challenges such as DC protection, the lack of natural zero crossing of the current, electric arc extinction and fault current interruption. Overall, the results of this thesis indicate that converting a low-voltage AC distribution cabinet to DC is a practical and achievable solution for future distribution networks.